PENGENDALIAN PERSEDIAAN BAHAN BAKU BROWNIES DENGAN ANALISIS PERBANDINGAN METODE MIN-MAX, ECONOMIC ORDER QUANTITY DAN PERIOD ORDER QUANTITY - Nurhasanah Nurhasanah; Rina Filia Sari; Hendra Cipta (LPPM Universitas Bina Bangsa, 2023)
This research examines raw material inventory control at Hendhy's Brownies. Inventory management analysis is carried out using the Min-Max, Economic Order Quantity (EOQ) and Period Order Quantity (POQ) methods. Based on data analysis and processing, it is known that raw material inventory management using the min-max method has an order quantity of 13,231 kg with an ordering frequency of 5 times and a total ordering cost of Rp. 5,325,387. By using the Economic Order Quantity (EOQ) method, an order quantity of 9001 kg was obtained with an order frequency of 5.3 times and a total order cost of Rp. 3,420,527 Using the Periodic Order Quantity (POQ) method, the order quantity is 4252 kg, the order frequency is 20 times, and the total order price is IDR 3,071,030. Based on the results of the three methods, the EOQ method is the most optimal inventory control method compared to the other two methods. So that the results obtained through the EOQ method can improve forecasting of raw material shortages for companies, so that the use of raw materials becomes optimal